Use of the Word Method (Whole Word Method) to Improve Beginning Reading Ability in Class 1 Students Of SDN 1 Mumbul Sari Year 2024/2025 - Hadi, Rusman (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This research aims to find out whether the word method can improve student learning outcomes at SDN 1 Mumbul Sari. This research was carried out at SDN 1 Mumbul Sari on class 1 students in the first semester of 2024/2025 with a total of 20 students consisting of 8 men and 12 women. This research is classroom action research carried out through 2 cycles, namely the First Cycle and the Second Cycle second. Type instruments used in this research were teacher and student observation sheets, learning outcomes tests, and documentation sheets. The data to be analyzed consists of individual completeness adjusted to KKM class 1 with a score >75 and classical completeness >80%. The results of the research in the first cycle, of the total number of 20 students, there were 11 students who were declared complete individually with an average score of 71.8. Meanwhile, there were 9 students who did not complete individually. Because in cycle I the students had not yet achieved the classical completion score, the research continued into cycle II. In cycle II classical completion reached 85% (18 students) with an average score of 79.1, while there were 2 students who were declared incomplete and obtained a score of 60. Thus it can be concluded that this research was declared complete because of the total number of students ( 20 people) there were >85% of students who obtained a KKM score (75) so that students were declared classically complete and the action was stopped in cycle II.